Early cystic relapse of embryonal carcinoma of testis in obturator fossa - (:unkn) unknown (My University, 2000)
OBJECTIVE: We report a case of embryonal carcinoma stage IIB arising from the right testis that subsequently underwent chemotherapy and retroperitoneal lymph node dissection and presented with an early cystic recurrence in the obturator fossa. METHODS: This case is reanalyzed retrospectively and literature is reevaluated for the early recurrences of testicular tumors at atypical locations. We discuss the rarity of obturator fossa as a location for early recurrences of testis tumors. RESULTS: Only one case of recurrence in obturator fossa has been reported. CONCLUSIONS: This case provides an example of the possibility of recurrence in an unpredictable short interval subsequent to proper therapies and underscores the importance of close follow-up.
Keywords: Adult; Humans; Male; Retrospective Studies; Lymphatic Metastasis; Testicular Neoplasms; Carcinoma, Embryonal